Grundtvig og genforeningen: En receptionshistorisk undersøgelse af kontinuitet og brud i fortolkningen af Grundtvigs syn på det sønderjyske spørgsmål - Pedersen, Kim Arne (Kirkehistoriske Samlinger, 2020)
Artiklen gennemfører en receptionshistorisk undersøgelse af fortolkningen af Grundtvigs stillingtagen til det problem, som Slesvigs statsretslige stilling og nationalt delte befolkning udgjorde i det 19. og 20. århundrede. Der spørges, om der er tale om kontinuitet eller brud imellem først Grundtvigs syn på det slesvigske spørgsmål og hans fortolkeres udlægninger af det, dernæst om, hvorvidt der er kontinuitet eller brud i selve disse fortolkninger. Der identificeres fire faser i fortolkningshistorien. Først 1864-1920, hvor fremstillingerne er præget af, at Slesvig er en del af Preussen og fra 1871 det forenede tyske kejserrige. Dernæst 1920-45, hvor genforeningen af Nordslesvig med Danmark og nazismens fremmarch sætter dagsordenen. Videre tiden efter 1945, hvor efterkrigstidens debat om, hvorvidt 1920-grænsen skulle rykkes længere sydpå, dominerer en række undersøgelser frem til og med 1950. Fra 1992 kan man tale om en ny fase, hvor forskningen i Grundtvig og Sønderjylland er bestemt af den nationale uro efter østblokkens sammenbrud, vitaliseringen af nationalismeforskningen i slutningen af 1980’erne og debatten om dansk national identitet fra 1992. Første og anden fase præges af kontinuitet: Grundtvig opfattes som tilhænger af den slesvigske befolknings selvbestemmelse, deling af Slesvig og respekt for områdets etnisk-nationale gruppers frihed i kirke og skole. En afgørende pointe i undersøgelsen er, at fortolkningerne af Grundtvigs holdninger her er afhængige af og bidrager til et billede af Danmark og da af den grundtvigske indflydelse på nationens liv som international model i henseende til ordningen af grænsespørgsmål, som frem til vor tid har spillet en afgørende rolle i dansk selvforståelse. Debatten om en mulig grænserevision efter 1945 bryder kontinuiteten, idet fortolkerne dels når til indsigt i, at Grundtvig under og efter den første slesvigske krig 1848-50 talte for fortsat dansk overhøjhed i Slesvig, dels er uenige om, hvorvidt han gik ind for hele Slesvigs indlemmelse i kongeriget, et »Danmark til Ejderen«. Gennem artikler af Grundtvig fra 1848 og til og med 1851 gøres rede for, at han i disse år grundlæggende fastholdt Danmarks overhøjhed i Slesvig, men at tanker om selvbestemmelse, deling af Slesvig og respekt for etnisk-nationale grupper samtidig forekommer i forfatterskabet. Med baggrund i udtalelser af Grundtvig i rollen som sin egen fortolker efter 1864 vises, at han under indtryk af løftet om en folkeafstemning i Slesvig i Pragerfreden efter den preussisk-østrigske krig 1866 tegnede et billede af sine hidtidige og aktuelle holdninger som præget af kontinuitet med selvbestemmelse og deling af Slesvig som grundlæggende synspunkter. Kontinuiteten i receptionshistorien frem til 1945 hviler således på Grundtvigs egen udlægning. Summary The article examines continuity and discontinuity in the reception of how Grundtvig wanted to solve, what in the 19. Century was called »det slesvigske eller sønderjyske spørgsmål« (the Schleswig problem): The Danish king was duke in Schleswig, and the population was divided between a Danish oriented and a German oriented group. The article deals with interpretations of Grundtvig’s proposals in his magazine »Danskeren« (the Dane) 1848-51 and after the Danish-German war 1864, and four phases in the history of interpretation are identified. The first phase falls between 1864 and 1920, where Schleswig was incorporated in Preussia and the German empire. The interpretators of Grundtvig, the grundtvigian folk high school principals Hans Rosendal (1839-1921) and Holger Begtrup (1859-1937), understand him as a supporter of a division of the land in accordance with the will of the Schleswigian population and as an advocate of respect for the national minorities in the area. Rosendals and Begtrup’s interpretations are linked to the fact, that the leader of the Danish movement in Schleswig, H.P. Hanssen Nørremølle (1862-1936), had a close relationship with the grundtvigian folk high school. The second phase comes in the years between the reunion of the Northern part of Schleswig with Denmark in 1920 and the end of World War Two in 1945. In this period, the Schleswigian grundtvigian politician Hans Jefsen Christensen (1880-1956) builds on Rosendal’s and Begtrup’s interpretations. Jefsen Christensen sees Grundtvig’s stress on freedom of the ethnic-national groups in Schleswig in religious and educational matters as a background for the way, the rights of the German minority are secured in Danish laws in the 1920s dealing with the reunion. For Jefsen Christensen, the influence of Grundtvig means that the Danish way of handling the situation in the borderland of Schleswig is a role model for other nations. Jefsen Christensen’s interpretation contains a hidden attack on the chauvinism of German Nazism in the period. The third phase is dominated by the Danish discussion on the possibility of moving the Danish border after the growth of the Danish movement in the German part of Schleswig in the years after 1945. Interpretators of Grundtvig debate, whether or not he supported the idea of a division of Schleswig in line with the wishes of the population in the area. Literary historian William Michelsen (1913-2001) follows Rosendal, Begtrup and Jefsen Christensen, stressing that Grundtvig did not support the idea of incorporating Schleswig as a whole in the kingdom of Denmark. Inside the grundtvigian folk high school movement, the followers of the principal Aage Møller (1885-1978) speaks for a revision of the border. In accordance with Møller, his disciple, the folk high school principal. MA Frede Bording (1908-1996) rejects the interpretation of Grundtvig as a supporter of the division of Schleswig as a result of the will of the population. In Bordings opinion, Grundtvig spoke for Danish supremacy in Schleswig. The jurist Axel Riishøj (1911-71) interprets Grundtvig in a partially similar way, but stresses, that Grundtvig did not want Schleswig to be a full part of the Danish kingdom against the wishes of the inhabitants of the land. He suggests, Grundtvig wanted the Schleswigian population to choose between incorporation in the Danish kingdom or authonomy under Danish supremacy after a period of preparation for the choice. In contrast, the historian Troels Fink (1912-99) stresses, that Grundtvig in the years after 1848 is moving towards a »Danmark til Ejderen«-position (Denmark to the river Eider), although he does not completely give up his opposition to a full incorporation of Schleswig in the kingdom of Denmark. The interpretators disagree, and the third phase means a break-up in the understanding of Grundtvig’s statements according to the Schleswig problem: discontinuity replaces the continual line before 1945. The fourth phase reflects the rise of nationalism in Eastern Europe after the breakdown of communism, the vitalizing of the research in nationalism in the end of the 1980s and the debate in Denmark about Danish national identity in and after 1992. The literary historian Flemming Lundgreen-Nielsen (1937-) follows Fink, arguing that Grundtvig from around 1850-51 to 1864 wants the Eider as the border of Denmark. The historian Jes Fabricius Møller (1966-) takes the opposite view, suggesting, that Grundtvig first after 1864 becomes a nationalist in the strict academic sense of the word, talking in favour of the correspondence of border and nationality. According to Fabricius Møller, Grundtvig first accepts the Schleswigian population’s right to decide for itself between Denmark and Germany after 1864. On the basis of the four phases, some of Grundtvigs own statements in Danskeren and after 1864 are examined. As early as 1848, he supported the idea of asking the population in Schleswig, whether or not it wanted to become a part of the Danish kingdom. During the following years he did not question the supremacy of Denmark in Schleswig due to the land’s status as a Danish dukedom. Nevertheless, he spoke for a division of the land in accordance with the population’s wishes as a prospect for the future in 1850. After 1864 Grundtvig becomes his own interpreter, stressing that he always had supported the right of the population in Schleswig to take its own decision in the national question. Grundtvig’s statement is an element in his promotion of a referendum in the area in accordance with a common accord between Preussia and Austria in 1866 (the Prag peace agreement). So, the line of Rosendal, Begtrup, Jefsen Christensen and Michelsen has Grundtvig’s own orchestration of his point of view according to the Schleswig problem as an important background.